Pengaruh PBL Berbantu Media Konkret Terhadap Hasil Belajar Nilai Tempat Bilangan Puluhan dan Satuan Kelas 2 Sekolah Dasar - Rustanti Ramadhani; Rasiman Rasiman; Anis Susilowati; Noviana Dini Rahmawati (Journal on Education, 2024)
This research aims to determine the effect of PBL assisted by concrete media on learning outcomes in place value of tens and units in grade 2 elementary school. This type of research is quantitative research in the form of pre-experimental design with one-group pretest and posttest design. The sample in this study was all 28 grade 2 students at SD Negeri Tawangmas 01. Using test data collection techniques (normality test, n-gain test, and paired sample t-test) and non-test (interviews and documentation). The results of this study obtained average pretest data of 58.93. while the average result of the posttest was 90.00. The results of the pretest and posttest Shapiro-Wilk normality test showed sig > 0.05 with pretest data 0.260 > 0.05 and posttest data 0.209 > 0.05 at a significance level of 0.05 and N = 28, so H0 was accepted. The n-gain test obtained was 0.7010. Stating the criteria for the N-Gain test value of 0.7 < g < 1 is categorized as high criteria. The Paired Sample T-Test obtained a significant value (2-tailed) of 0.000 < 0.005 so that Ho was rejected and Ha was accepted. The conclusion is that PBL assisted by concrete media has an effect on the learning outcomes of place value of tens and units in grade 2 of elementary school. This can be seen from student learning outcomes before and after being given treatment.